N, P, and S Codoped Graphene‐Like Carbon Nanosheets for Ultrafast Uranium (VI) Capture with High Capacity. Issue 10 (27th August 2018) - Chen, Zhe; Chen, Wanying; Jia, Dashuang; Liu, Yang; Zhang, Anrui; Wen, Tao; Liu, Jian; Ai, Yuejie; Song, Weiguo; Wang, Xiangke
Abstract: The development of functional materials for the highly efficient capture of radionuclides, such as uranium from nuclear waste solutions, is an important and challenging topic. Here, few‐layered N, P, and S codoped graphene‐like carbon nanosheets (NPS‐GLCs) that are fabricated in the 2D confined spacing of silicate RUB‐15 and applied as sorbents to remove U(VI)ions from aqueous solutions are presented. The NPS‐GLCs exhibit a large capacity, wide pH suitability, an ultrafast removal rate, stability at high ionic strengths, and excellent selectivity for U(VI) as compared to multiple competing metal ions. The 2D ultrathin structure of NPS‐GLCs with large spacing of 1 nm not only assures the rapid mass diffusion, but also exposes a sufficient active site for the adsorption. Strong covalent bonds such as POU and SOU are generated between the heteroatom (N, P, S) with UO2 2+ according to X‐ray photoelectron spectroscopy analysis and density functional theory theoretical calculations. This work highlights the interaction mechanism of low oxidation state heteroatoms with UO2 2+, thereby shedding light on the material design of uranium immobilization in the pollution cleanup of radionuclides. Abstract : Few‐layered N, P, and S codoped graphene‐like carbon nanosheets are produced in the 2D confined spacing of silicate RUB‐15. With the aid of X‐ray photoelectron spectroscopy analysis and density functional theory calculation, the strong covalent bonds (POU and SOU) are proved to be the key for the excellent performance and selectivity on UO2 2+ fixation.